Construction and Governance of Transnational Higher Education Research Partnerships in Kenya and Uganda - Nyerere, Jackline (Papers in Education and Development, 2020)
This study was designed to critically examine and evaluate the organisation, policy frameworks and governance structures of transnational research partnerships in six universities in Kenya and Uganda, and how they interface with national development. Traditionally, universities in the two countries have embraced transnational partnerships mostly as a source of revenue and academic capacity building. The focus has since then shifted to enhancing institutional reputation and ranking. Findings show that the study universities have put in place structures that govern the partnerships. Some benefits associated with transnational partnerships in these universities are building teaching and research capacity and development of curriculum. Challenges experienced include inadequate funding and low university investment in research in both Kenya and Uganda. Keywords: governance, research, transnational partnerships